2022
DOI: 10.1021/acs.energyfuels.2c02121
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of Alkanes by Organometallics in an In Situ Combustion Process

Abstract: The complicated composition of crude oils increases the difficulties in understanding their complex oxidation mechanism and catalysis in an air injection enhanced oil recovery (EOR) process, which therefore makes it necessary to use oil components as study objects. In this work, n-hexadecane (C16H34) was used as the representative of saturates to study its catalytic oxidation using oil-dispersed organometallics as catalysts. Its exothermic reaction behavior and kinetics during the oxidation process were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…On one hand, by reducing the content of heavy components such as alkanes above C 22 , resins, and asphaltenes and increasing the content of light components such as alkanes below C 21 and aromatics, the average molecular weight of crude oil is reduced. On the other hand, the desulphurization and denitrification reactions can reduce the heteroatom content in crude oil and reduce intermolecular forces to achieve a substantial irreversible viscosity reduction in heavy oil [37][38][39][40][41][42].…”
Section: In-situ Upgrading Of Heavy Oilmentioning
confidence: 99%
“…On one hand, by reducing the content of heavy components such as alkanes above C 22 , resins, and asphaltenes and increasing the content of light components such as alkanes below C 21 and aromatics, the average molecular weight of crude oil is reduced. On the other hand, the desulphurization and denitrification reactions can reduce the heteroatom content in crude oil and reduce intermolecular forces to achieve a substantial irreversible viscosity reduction in heavy oil [37][38][39][40][41][42].…”
Section: In-situ Upgrading Of Heavy Oilmentioning
confidence: 99%
“…In 2022, Yuan et al found similar results, when evaluating the performance of γ-Fe 2 O 3 catalysts by using thermal effect cells in porous medium (PMTEC). In a similar work, the same group developed the catalytic oxidation of alkanes by organometallics in an ISC process . The stabilization of the combustion front via bimetallic Mn@Cu tallates during crude oil oxidation was also explored .…”
Section: Introductionmentioning
confidence: 99%
“…In a similar work, the same group developed the catalytic oxidation of alkanes by organometallics in an ISC process. 34 The stabilization of the combustion front via bimetallic Mn@Cu tallates during crude oil oxidation was also explored. 35 Furthermore, the mechanistic and kinetic study was performed for a catalytic ISC of a heavy crude oil.…”
Section: Introductionmentioning
confidence: 99%